2021
DOI: 10.5114/pjr.2021.106470
|View full text |Cite
|
Sign up to set email alerts
|

Can imaging suggest the aetiology in skull base osteomyelitis? A systematic literature review

Abstract: IntroductionTo assess differentiating features between bacterial, Aspergillus, and Mucor skull base osteomyelitis (SBO) with regard to clinical presentation and imaging appearances.Material and methodsA literature search was performed in April 2020 for studies on SBO with a minimum sample size of 10 patients. Studies that reported presenting symptoms, cross-sectional imaging findings, complications, and mortality were included in the analysis. The quality of included articles was tested using the Quality Asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Diagnosis of mucormycosis and aspergillosis is achieved based on the clinical features, DNE (diagnostic nasal endoscopy) radiology (CE-MRI/CECT) [13] , histopathological and microbiological analysis. The bacterial and fungal osteomyelitis don’t differ in their radiology (CE-MRI/CECT) imaging findings; however according to a study by Deeksha Bhalla et al, the bacterial skull base osteomyelitis (SBO) presents with bone erosion in the later stage along with lesser extent of bony erosion compared to fungal SBO [14] . Other advanced aids include Immunohistochemistry, In-situ hybridization, Polymerase chain reaction (PCR) based molecular identification of DNA sequencing based on bar codes 18 S, ITS,28 s, rDNA, MALDI‑TOF [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of mucormycosis and aspergillosis is achieved based on the clinical features, DNE (diagnostic nasal endoscopy) radiology (CE-MRI/CECT) [13] , histopathological and microbiological analysis. The bacterial and fungal osteomyelitis don’t differ in their radiology (CE-MRI/CECT) imaging findings; however according to a study by Deeksha Bhalla et al, the bacterial skull base osteomyelitis (SBO) presents with bone erosion in the later stage along with lesser extent of bony erosion compared to fungal SBO [14] . Other advanced aids include Immunohistochemistry, In-situ hybridization, Polymerase chain reaction (PCR) based molecular identification of DNA sequencing based on bar codes 18 S, ITS,28 s, rDNA, MALDI‑TOF [15] .…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known on the differences in CT and MRI characteristics between fungal and bacterial TBO. A small review of fungal skull base osteomyelitis (both otogenic and sinogenic) found that fungal TBO occasionally appears on MRI as T2 hypointensity with blooming on gradient echo sequences due to the concentration of ferromagnetic elements during fungal metabolism (93). Adjunctive imaging with nuclear medicine studies were less commonly used in our review, most likely because of the lack of widespread availability, expense, time commitment, and radiation exposure (15).…”
Section: Diagnosismentioning
confidence: 99%
“…Diffusion restriction can be seen in localized abscesses. Fungal infections however can demonstrate conspicuous T2 hypointensity with blooming on gradient sequences (from the presence of ferromagnetic elements – iron, zinc, manganese) [24 ▪▪ ].…”
Section: Imaging Findings and Role Of Different Modalitiesmentioning
confidence: 99%
“…Polymicrobial infection is also noted. Fungal infections could occur in the absence of immunosuppression [24 ▪▪ ,38,39 ▪▪ ].…”
Section: Etiology and Causative Organismsmentioning
confidence: 99%
See 1 more Smart Citation